2022
DOI: 10.3390/biomedicines10102379
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Endothelium and the Cardiometabolic Patient: A Possible Role for Capillary Leak Syndrome

Abstract: Capillary leak syndrome is an under-diagnosed condition leading to serious hypoalbuminemia with diffuse edema, pulmonary edema, severe hypotension, and possibly death. Sepsis leading to hemophagocytic lymphohistiocytosis (HLH) is a major risk factor; however, capillary hyper-permeability is the core underlying pathophysiological mechanism. Endothelial dysfunction plays a major role in cardiometabolic disease through insulin resistance, lipotoxicity, and, eventually, oxidative stress and chronic inflammation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that inflammation can increase capillary permeability, allowing serum albumin to escape into the interstitial space, thereby expanding the interstitial volume and increasing the distribution volume of albumin ( Dekker et al, 2018 ). This heightened capillary permeability serves as a key mechanism through which inflammation leads to the escape of serum albumin, ultimately resulting in hypoalbuminemia ( Lambadiari et al, 2022 ). Additionally, inflammation can induce hypoalbuminemia by promoting the catabolism of albumin in response to infection-related inflammation ( Arnau-Barrés et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that inflammation can increase capillary permeability, allowing serum albumin to escape into the interstitial space, thereby expanding the interstitial volume and increasing the distribution volume of albumin ( Dekker et al, 2018 ). This heightened capillary permeability serves as a key mechanism through which inflammation leads to the escape of serum albumin, ultimately resulting in hypoalbuminemia ( Lambadiari et al, 2022 ). Additionally, inflammation can induce hypoalbuminemia by promoting the catabolism of albumin in response to infection-related inflammation ( Arnau-Barrés et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thrombosis and DIC are vascular events that are actively involved in the progression of COVID-19 and represent a coagulation/fibrinolytic abnormality manifested by macroand microthrombotic events. The likelihood of the occurrence of COVID-19 thrombosis increases with increased markers of coagulation and fibrinolysis [144,145].…”
Section: Dic and Thrombosis In Covid-19 Casesmentioning
confidence: 99%
“…Furthermore, oxidative stress is characterized by the production of peroxynitrite that down-regulates NO bioavailability and leads to vasoconstriction. Also, the accumulation of ROS promotes the apoptosis of ECs and augment the expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin resulting in microvascular inflammation and hypercoagulability [180]. Chronic inflammation inhibits the production of endothelial eNOS and promotes the expression of ICAM-1, VCAM-1 and ET-1, further damaging endothelial integrity [181].…”
Section: Diabetesmentioning
confidence: 99%